USE OF CRISPR BASE EDITING AND PRIME EDITING IN NEUROLOGICAL DISEASES - Gaion Malosso, Milena; de Souza Batalha, Eriana; Monteiro dos Santos, Ivan; dos Santos Faria, Ricardo (Health and Society, 2025)
Next-generation gene editing technologies, particularly base editing and prime editing, have emerged as highly promising approaches for the treatment of neurological diseases driven by pathogenic mutations and genomic instability. Unlike conventional CRISPR-Cas9 methods that introduce double-strand breaks, these systems enable precise nucleotide conversions or guided sequence replacements, thereby reducing off-target events and increasing safety for central nervous system (CNS) applications. Recent studies demonstrate their applicability in cellular and animal models of conditions such as Alternating Hemiplegia of Childhood, Huntington’s disease, and repeat-associated ataxias, showing functional restoration, decreased somatic repeat expansion, and improvement of neurological phenotypes. However, the clinical translation of these tools still faces substantial challenges, including limitations in CNS delivery, target-dependent efficiency, and the need for comprehensive biosafety evaluation. Viral and nonviral platforms—such as optimized AAVs, lipid nanoparticles, and virus-like particles—are under active development to overcome these barriers. Additional gaps remain regarding editing durability, immunogenicity, and scalability. This article provides an integrated analysis of the principles, preclinical applications, technical limitations, and future perspectives of base editing and prime editing in neurological diseases, emphasizing their transformative potential and the necessity of rigorous, safety-driven research.